2017
DOI: 10.2139/ssrn.2980877
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Foreign Aid for Inclusive Human Development in Africa

Abstract: In the light of evidence that poverty has been decreasing in all regions of the World with the exception of Africa, where about 45 percent of countries in Sub-Saharan Africa did not achieve the Millennium Development Goal (MDG) extreme poverty target. Therefore, this study assesses whether increasing foreign aid improves inclusive human development. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…However, to avoid proliferation or over-identification of instruments which causes biasedness of GMM estimator, over-fitting of endogenous variables, weakening of Sargan/Hansen test, the rule of thumb is that the number of instruments should not be higher than the number of periods in cross sections (Asongu and Nwachukwu, 2017). However, Roodman (2009) suggested that in order to avoid proliferation of instruments, the number of instruments should not exceed the number of groups (cross-section).…”
Section: Methodsmentioning
confidence: 99%
“…However, to avoid proliferation or over-identification of instruments which causes biasedness of GMM estimator, over-fitting of endogenous variables, weakening of Sargan/Hansen test, the rule of thumb is that the number of instruments should not be higher than the number of periods in cross sections (Asongu and Nwachukwu, 2017). However, Roodman (2009) suggested that in order to avoid proliferation of instruments, the number of instruments should not exceed the number of groups (cross-section).…”
Section: Methodsmentioning
confidence: 99%
“…With this in mind, we focus on South Asian countries to examine the link between AID and health outcomes. 3 Our approach is similar to Bhaumik (2005), , Askarov and Doucouliagos (2015) and Asongu and Nwachukwu (2018) in focusing on the effectiveness of aid in countries that share similar geographical and economic characteristics. 4 The examination of the South Asian experience is motivated by two factors.…”
Section: Introductionmentioning
confidence: 99%